PENGARUH CURRENT RATIO, RETURN ON EQUITY DAN DEBT TO EQUITY RATIO TERHADAP HARGA SAHAM PADA PT ASTRA INTERNATIONAL TBK PERIODE 2013-2022 - Deliana, Viona; Syakhrial (Journal of Research and Publication Innovation, 2024)
This study aims to examine the impact of Current Ratio, Return On Equity (ROE), and Debt To Equity Ratio (DER) both partially and simultaneously on the stock price of PT Astra International Tbk for the period 2013-2022. The population selected is the financial statements of PT Astra International Tbk for the period 2013-2022, with the samples used being the balance sheet, income statement, and stock overview for the same period. The research employed is quantitative. The data analysis techniques used include descriptive analysis, classical assumption tests, multiple linear regression, hypothesis testing, and coefficient of determination. Based on the results of the t-test, Current Ratio has a negative and significant effect on stock prices with a significance value of 0.007 < 0.05 and a t-value of -4.076 > t-table of 2.447. Return On Equity does not have an effect on stock prices with a significance value of 0.396 > 0.05 and a t-value of -0.914 < 2.447. Debt To Equity Ratio also does not have an effect on stock prices with a significance value of 0.246 > 0.05 and a t-value of -1.286 < 2.447. Simultaneous testing (F-test) indicates that Current Ratio, Return On Equity, and Debt To Equity Ratio have a significant effect on stock prices with a significance value of 0.011 < 0.05 and an F-value of 9.518 > F-table of 4.760. According to the coefficient of determination, the effect of Current Ratio, Return On Equity, and Debt To Equity Ratio on stock prices is 74%, while the remaining 26% is influenced by other variables not examined in this study.